Analysis of Banking Performance in The Aftermath of The Merger of Bank Syariah Indonesia in Covid 19 - Mohammad Yusuf; Reza Nurul Ichsan (International Journal of Science, Technology & Management, 2021)
This study aims to determine sharia banking performance after the merger of Sharia Banks and Covid 19 pendemi by looking at the influence of NPF, FDR, BOPO, and CAR financial performance of Sharia Commercial Banks in the Period 2011-2020. This research uses quantitative research method with population in this research is all sharia commercial banks in Indonesia period 2011-2020. Data collection is done by library method from journal, article, or literature related to the required data, and documentation method of sharia commercial bank implementation report in question as well as data from OJK website. The research method used is a statistical descriptive test, descriptive test by analyzing ROA through ROA implementation report using content analysis method, classic assumption test, some regression test. Results show that the variables NPF, FDR, BOPO, and CAR are simultaneously financial performance of Sharia Commercial Banks in Indonesia in the period 2011-2020. Simultaneously, the variables of NPF, FDR, BOPO and CAR have a significant impact on the financial performance (ROA) of sharia commercial banks in Indonesia in the period 2011-2020. Based on the amount adjusted R2 is 0.979 which means that 97.9% of financial performance (ROA) of sharia commercial banks is influenced by independent variables, while 02.1% is influenced by other factors outside the research. Car partially had an insignificant positive effect on the financial performance (ROA) of sharia commercial banks in Indonesia in the period 2011-2020. Partially, NPF has an insignificant positive effect on the financial performance (ROA) of sharia commercial banks in Indonesia in the period 2011-2020. Partially BOPO has a significant negative effect on the financial performance (ROA) of sharia commercial banks in Indonesia in the period 2011-2020. Partially, FDR has an insignificant positive effect on the financial performance (ROA) of sharia commercial banks in Indonesia in the period 2011-2020.